Assessing food consumption discrepancy between food balance sheet and survey dietary data in Europe - Silvestre García de Jalón; Luis Garrote; Simona Castaldi; Laure Berling; Ana Iglesias (Food and Humanity, 2026)

Salinization in groundwater vulnerability: A review of GALDIT-Based methods - Mojgan Bordbar; Gianluigi Busico; Nebojsa Jovanovic; Beata Jaworska-Szulc; Adam Szymkiewicz; Simona Castaldi; Konstantinos Chalikakis; Ricardo Hirata; Micòl Mastrocicco (Groundwater for Sustainable Development, 2026)

Enhancing ecosystem services by introducing multifunctional land use management in a semiarid pastoral system in Portugal - H.K. Ishaq; Eleonora Grilli; Gianluigi Busico; Micòl Mastrocicco; F.A. Rutigliano; Marco Bijl; Simona Castaldi (Total Environment Advances, 2025)

Enhancing soil health with hydrochar: Improvements in chemical and biological properties - Teresa Di Santo; Rossana Marzaioli; Elio Coppola; Lucio Zaccariello; Daniele Battaglia; Simona Castaldi; Rosaria D'Ascoli; Stefania Papa; Sandro Strumia; Giovanna Battipaglia; Luigi Morra; Maria L. Mastellone; et al. (Journal of Environmental Management, 2025)

Soil quality under rotational and conventional grazing in Mediterranean areas at desertification risk - Hafiz Khuzama Ishaq; Eleonora Grilli; Rosaria D'Ascoli; Micol Mastrocicco; Angela Flora Rutigliano; Rossana Marzaioli; Sandro Strumia; Elio Coppola; Iseult Malrieu; Filipe Silva; Simona Castaldi (Journal of Environmental Management, 2025)

Intrinsically disordered Prosystemin discloses biologically active repeat motifs - Valeria Castaldi; Emma Langella; Martina Buonanno; Ilaria Di Lelio; Anna Maria Aprile; Donata Molisso; Martina Chiara Criscuolo; Luca Domenico D'Andrea; Alessandra Romanelli; Angela Amoresano; Gabriella Pinto; Anna Illiano; et al. (Plant Science, 2024)

Effects of wildfire on growth, transpiration and hydraulic properties of Pinus pinaster Aiton forest - Francesco Niccoli; Arturo Pacheco-Solana; Sylvain Delzon; Jerzy Piotr Kabala; Shahla Asgharinia; Simona Castaldi; Riccardo Valentini; Giovanna Battipaglia (Dendrochronologia, 2023)

Weakened growth of cropland‐N 2 O emissions in China associated with nationwide policy interventions - Ziyin Shang; Feng Zhou; Pete Smith; Eri Saikawa; Philippe Ciais; Jinfeng Chang; Hanqin Tian; Stephen J. Del Grosso; Akihiko Ito; Minpeng Chen; Qihui Wang; Yan Bo; et al. (Global Change Biology, 2019)
China has experienced rapid agricultural development over recent decades, accompanied by increased fertilizer consumption in croplands; yet, the trend and drivers of the associated nitrous oxide (N 2 O) emissions remain uncertain. The primary sources of this uncertainty are the coarse spatial variation of activity data and the incomplete model representation of N 2 O emissions in response to agricultural management. Here, we provide new data‐driven estimates of cropland‐N 2 O emissions across China in 1990–2014, compiled using a global cropland‐N 2 O flux observation dataset, nationwide survey‐based reconstruction of N‐fertilization and irrigation, and an updated nonlinear model. In addition, we have evaluated the drivers behind changing cropland‐N 2 O patterns using an index decomposition analysis approach. We find that China's annual cropland‐N 2 O emissions increased on average by 11.2 Gg N/year 2 ( p 2 , p = .02), consistent with the output from an ensemble of process‐based terrestrial biosphere models. The slowdown of the increase in cropland‐N 2 O emissions after 2003 was pervasive across two thirds of China's sowing areas. This change was mainly driven by the nationwide reduction in N‐fertilizer applied per area, partially due to the prevalence of nationwide technological adoptions. This reduction has almost offset the N 2 O emissions induced by policy‐driven expansion of sowing areas, particularly in the Northeast Plain and the lower Yangtze River Basin. Our results underline the importance of high‐resolution activity data and adoption of nonlinear model of N 2 O emission for capturing cropland‐N 2 O emission changes. Improving the representation of policy interventions is also recommended for future projections.

Postfire nitrogen balance of Mediterranean shrublands: Direct combustion losses versus gaseous and leaching losses from the postfire soil mineral nitrogen flush - Michael Dannenmann; Eugenio Díaz‐Pinés; Barbara Kitzler; Kristiina Karhu; Javier Tejedor; Per Ambus; Antonio Parra; Laura Sánchez‐Martin; Victor Resco; David A. Ramírez; Luciano Povoas‐Guimaraes; Georg Willibald; et al. (Global Change Biology, 2018)
Fire is a major factor controlling global carbon (C) and nitrogen (N) cycling. While direct C and N losses caused by combustion have been comparably well established, important knowledge gaps remain on postfire N losses. Here, we quantified both direct C and N combustion losses as well as postfire gaseous losses (N 2 O, NO and N 2 ) and N leaching after a high‐intensity experimental fire in an old shrubland in central Spain. Combustion losses of C and N were 9.4 Mg C/ha and 129 kg N/ha, respectively, representing 66% and 58% of initial aboveground vegetation and litter stocks. Moreover, fire strongly increased soil mineral N concentrations by several magnitudes to a maximum of 44 kg N/ha 2 months after the fire, with N largely originating from dead soil microbes. Postfire soil emissions increased from 5.4 to 10.1 kg N ha −1 year −1 for N 2 , from 1.1 to 1.9 kg N ha −1 year −1 for NO and from 0.05 to 0.2 kg N ha −1 year −1 for N 2 O. Maximal leaching losses occurred 2 months after peak soil mineral N concentrations, but remained with 0.1 kg N ha −1 year −1 of minor importance for the postfire N mass balance. 15 N stable isotope labelling revealed that 33% of the mineral N produced by fire was incorporated in stable soil N pools, while the remainder was lost. Overall, our work reveals significant postfire N losses dominated by emissions of N 2 that need to be considered when assessing fire effects on ecosystem N cycling and mass balance. We propose indirect N gas emissions factors for the first postfire year, equalling to 7.7% (N 2 ‐N), 2.7% (NO‐N) and 5.0% (N 2 O‐N) of the direct fire combustion losses of the respective N gas species.

Tree-ring carbon and oxygen isotopes indicate different water use strategies in three Mediterranean shrubs at Capo Caccia (Sardinia, Italy) - Simona Altieri; Simone Mereu; Paolo Cherubini; Simona Castaldi; Carmina Sirignano; Carmine Lubritto; Giovanna Battipaglia (Trees, 2015)

Inhibition of net nitrification activity in a Mediterranean woodland: possible role of chemicals produced by Arbutus unedo - Simona Castaldi; Anna Carfora; Antonio Fiorentino; Angela Natale; Anna Messere; Franco Miglietta; M. Francesca Cotrufo (Plant and Soil, 2009)

Fluxes of N 2 O and CH 4 from soils of savannas and seasonally‐dry ecosystems - Simona Castaldi; Antonella Ermice; Sandro Strumia (Journal of Biogeography, 2006)
Aim Savannas and seasonally‐dry ecosystems cover a significant part of the world's land surface. If undisturbed, these ecosystems might be expected to show a net uptake of methane (CH 4 ) and a limited emission of nitrous oxide (N 2 O). Land management has the potential to change dramatically the characteristics and gas exchange of ecosystems. The present work investigates the contribution of warm climate seasonally‐dry ecosystems to the atmospheric concentration of nitrous oxide and methane, and analyses the impact of land‐use change on N 2 O and CH 4 fluxes from the ecosystems in question. Location Flux data reviewed here were collected from the literature; they come from savannas and seasonally‐dry ecosystems in warm climatic regions, including South America, India, Australasia and Mediterranean areas. Methods Data on gas fluxes were collected from the literature. Two factors were considered as determinants of the variation in gas fluxes: land management and season. Land management was grouped into: (1) control, (2) ‘burned only’ and (3) managed ecosystems. The season was categorized as dry or wet. In order to avoid the possibility that the influence of soil properties on gas fluxes might confound any differences caused by land management, sites were grouped in homogeneous clusters on the basis of soil properties, using multivariate analyses. Inter‐ and intra‐cluster analysis of gas fluxes were performed, taking into account the effects of season, land management and main vegetation types. Results Soils were often acid and nutrient‐poor, with low water retention. N 2 O emissions were generally very low (median flux 0.32 mg N 2 O m −2 day −1 ), and no significant differences were observed between woodland savannas and managed savannas. The highest fluxes (up to 12.9 mg N 2 O m −2 day −1 ) were those on relatively fertile soils with high air‐filled porosity and water retention. The effect of season on N 2 O production was evident only when sites were separated in homogeneous groups on the basis of soil properties. CH 4 fluxes varied over a wide range (−22.9 to 3.15 mg CH 4 m −2 day −1 , where the negative sign denotes removal of gas from the atmosphere), with an annual average daily flux of −0.48 ± 0.96 (SD) mg CH 4 m −2 day −1 in undisturbed (control) sites. Land‐use change dramatically reduced this CH 4 sink. Managed sites were weak sinks of CH 4 in the dry season and became sources of CH 4 in the wet season. This was particularly evident for pastures. Burning alone did not reduce soil net CH 4 oxidation, but decreased N 2 O production. Main conclusions Despite the low potential for N 2 O production, both in natural and managed conditions, tropical seasonally‐dry ecosystems represent a significant source of N 2 O (4.4 Tg N 2 O year −1 ) on a global scale, as a consequence of the large area they occupy. The same environments represent a potential CH 4 sink of 5.17 Tg CH 4 year −1 . However, assuming that c. 30% of the tropical land is converted to different uses, the sink would be reduced to 3.2 Tg CH 4 year −1 . The limited information on fluxes from Mediterranean ecosystems does not allow a meaningful scaling up.

Cycloheximide inhibition of peptone-induced nitrate production across a soil moisture gradient - Simona Castaldi (Biology and Fertility of Soils, 2005)

Soil-Atmosphere Methane Exchange in Undisturbed and Burned Mediterranean Shrubland of Southern Italy - Simona Castaldi; Angelo Fierro (Ecosystems, 2005)

Nitrous oxide and methane fluxes from soils of the Orinoco savanna under different land uses - Castaldi Simona; De Pascale Raffaele Ariangelo; Grace John; Nikonova Nina; Montes Ruben; San José José (Global Change Biology, 2004)
The study investigates the effect of land‐use change on nitrous oxide (N 2 O) and methane (CH 4 ) fluxes from soil, in savanna ecosystems of the Orinoco region (Venezuela). Gas fluxes were measured by closed static chambers, in the wet and dry season, in representative systems of land management of the region: a cultivated pasture, an herbaceous savanna, a tree savanna and a woodland (control site). Higher N 2 O emissions were observed in the cultivated pasture and in the herbaceous savanna compared with the tree savanna and the woodland, and differences were mainly related to fine soil particle content and soil volumetric water content measured in the studied sites. Overall N 2 O emissions were quite low in all sites (0–1.58 mg N 2 O‐N m −2 day −1 ). The cultivated pasture and the woodland savanna were on average weak CH 4 sinks (−0.05±0.07 and −0.08±0.05 mg CH 4 m −2 day −1 , respectively), whereas the herbaceous savanna and the tree savanna showed net CH 4 production (0.23±0.05 and 0.19±0.05 mg CH 4 m −2 day −1 , respectively). Variations of CH 4 fluxes were mainly driven by variation of soil water‐filled pore space (WFPS), and a shift from net CH 4 consumption to net CH 4 production was observed at around 30% WFPS. Overall, the data suggest that conversion of woodland savanna to managed landscape could alter both CH 4 and N 2 O fluxes; however, the magnitude of such variation depends on the soil characteristics and on the type of land management before conversion.

Suitability of soil microbial parameters as indicators of heavy metal pollution - Castaldi Simona; Rutigliano Flora Angela; Virzo de Santo Amalia (Water, Air, & Soil Pollution, 2004)

Factors influencing nitrification and denitrification variability in a natural and fire-disturbed Mediterranean shrubland - Simona Castaldi; Danilo Aragosa (Biology and Fertility of Soils, 2002)

The effect of different N substrates on biological N2O production from forest and agricultural light textured soils - Simona Castaldi; Keith A. Smith (Plant and Soil, 1998)